Combined Effects of Listening to Preferred Music and Video Feedback, during Warm-Up, on Physical Performance in Young Kickboxers - Manar Boujabli; Nidhal Jebabli; Faten Sahli; Hajer Sahli; Makram Zghibi; Roland van den Tillaar (MDPI AG, 2024)
Although studies have indicated that the prior use of video feedback and music listening separately improves physical performance and positive feelings in various sports, to our knowledge, no studies have investigated their combined effect in combat-sports-specific tasks. The aim of this study was to determine the combined effect of listening to preferred music and video feedback on aerobic and anaerobic performance in male kickboxers. In a counterbalanced crossover study design, twenty kickboxers underwent three kicking exercises under one of three conditions: (1) control condition, (2) combined listening to preferred music and video feedback, and (3) video feedback during 10-min of rope warm-up. Kickboxers performed a ten-second kicking test, multiple ten-second kick test, and progressive taekwondo test. The total number of kicks, fatigue index, heart rate, rate of perceived exertion, and feeling scale were measured. The combined music and video feedback condition improved the number of kicks with a better positive feeling scale (F ≥ 7.4, p ≤ 0.002, ηp2 ≥ 0.28) than the video feedback and control conditions in all three kicking exercises, while the video feedback alone led to better kick performances and a better feeling scale than the control condition in the ten-second and multiple ten-second kicking tests (p ≤ 0.016). The combined listening to preferred music and video feedback condition was more effective at enhancing the positive feeling scale and repeated roundhouse kick performance. Future investigations should examine the application of video feedback and listening to music in various kickboxing tasks including punches and kicks.